Analgesia-free flexible ureteroscopic treatment and laser lithotripsy for removal of a large urinary stone: a case report. (December 2015) - Wilhelm, Konrad; Frankenschmidt, Alexander; Miernik, Arkadiusz
Abstract Introduction Urinary stone formation is a frequent complication after continent urinary tract diversion and can require complex surgical management. Therapy options include open, percutaneous, transurethral, or transstomal stone fragmentation and extraction. The transstomal approach is considered to be one of the more complex treatment modalities. The patient's individual anatomy, minor stoma diameter, and the existing continence mechanism in the majority of cases cause substantial technical challenges for the surgeon. We present here what we believe to be the first description of an analgesia-free flexible endoscopic removal of a large pouch stone in an out-patient care setting. Additionally, we provide a brief overview of competing techniques. Case presentation A 30-year-old Caucasian woman with a history of lower urinary tract reconstruction with an ileal pouch and a continent umbilical stoma was admitted to our department with pouch urolithiasis in the urinary reservoir. We employed a minimally invasive approach to extract the stone using flexible ureteroscopy via a modified access sheath and laser lithotripsy. No analgesia is needed with this procedure and it can be performed in an out-patient setting. Conclusion The described clinical case highlights the difficulties of treating this high-incidence problem in patients with continent urinary diversions. Our presented technique is of particular interest to urologists and family doctors, and could improve the treatment of such patients by lowering the morbidity of the intervention.